Abcharis nom. nov., a new substitute name for Notiocharis Eaton, 1913 (Diptera: Psychodidae: Psychodinae) with world check-list of species - Tkoč, Michal; Ježek, Jan (Zootaxa, 2013)
Abcharis nom. nov. is established as a new substitute name for Notiocharis Eaton, 1913 (Diptera: Psychodidae: Psychodinae), which is a junior homonym of Notiocharis Gistel, 1856 (Coleoptera: Carabidae). The following new combinations are proposed: Abcharis assimilis (Quate & Quate, 1967) comb. nov.; A. dimorpha (Satchell, 1953) comb. nov.; A. femoralis (Quate, 1965) comb. nov.; A. filipinae (Quate, 1965) comb. nov.; A. fragilis (Quate & Quate, 1967) comb. nov.; A. insignis (Eaton, 1913) comb. nov.; A. kalabakensis (Quate, 1962) comb. nov.; A. lanceolata (Quate & Quate, 1967) comb. nov.; A. maai (Quate & Quate, 1967) comb. nov.; A. mangrophila (Ježek, 2000) comb. nov.; A. miranda (Quate & Quate, 1967) comb. nov.; A. pallida (Satchell, 1953) comb. nov.; A. papuensis (Quate & Quate, 1967) comb. nov.; A. paxillosa (Quate & Quate, 1967) comb. nov.; A. phlyctis (Quate & Quate, 1967) comb. nov.; A. sarawakensis (Quate, 1962) comb. nov.; A. stellae (Quate, 1962) comb. nov.; and A. wilsoni (Duckhouse, 1966) comb. nov. A world checklist of the included species with information about type material and distribution is provided.